2017
DOI: 10.1002/jso.24596
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative chemotherapy versus neoadjuvant chemoradiotherapy for esophageal or GEJ adenocarcinoma: A propensity score‐matched analysis comparing toxicity, pathologic outcome, and survival

Abstract: Compared to perioperative chemotherapy, neoadjuvant chemoradiotherapy achieves higher pathologic response rates and a lower risk of locoregional disease progression, without improving survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
22
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 46 publications
5
22
2
Order By: Relevance
“…In the majority of previous studies, a similar prognosis was demonstrated between the PCRT and the POC groups, a finding that contradicts the results published by Tian et al Furthermore, if we focused on the patient with a T3 to T4 tumor, PCRT might have a positive influence on survival. For example, Stahl et al reported that in the Preoperative chemotherapy versus chemoradiotherapy in locally advanced adenocarcinomas of the oesophagogastric junction (POET) trial (in which only patients with T3‐T4 tumors were included), the PCRT group had a significantly improved progression‐free survival (hazard ratio [HR], 0.37; P = .01) and the overall survival (OS) also demonstrated a positive trend (HR, 0.65; P = .055).…”
contrasting
confidence: 77%
“…In the majority of previous studies, a similar prognosis was demonstrated between the PCRT and the POC groups, a finding that contradicts the results published by Tian et al Furthermore, if we focused on the patient with a T3 to T4 tumor, PCRT might have a positive influence on survival. For example, Stahl et al reported that in the Preoperative chemotherapy versus chemoradiotherapy in locally advanced adenocarcinomas of the oesophagogastric junction (POET) trial (in which only patients with T3‐T4 tumors were included), the PCRT group had a significantly improved progression‐free survival (hazard ratio [HR], 0.37; P = .01) and the overall survival (OS) also demonstrated a positive trend (HR, 0.65; P = .055).…”
contrasting
confidence: 77%
“…[19][20][21][22] The latter is particularly true for those with advanced disease that cannot be cured with surgery alone. In these patients, more emphasis should be placed on how and when to perform chemoradiation; [23][24][25][26][27][28] attempting to obtain a low LNR or SR, which may lead to excessive lymphadenectomy and further increase the incidence of postoperative complications with no demonstrable survival benefit. Therefore, these findings encourage us to explore the optimal extent of surgical resection for each tumor status via further study, and it is possible that survival could be maximized if nodal status could be predicted more precisely.…”
Section: Comparison Of the Prognostic Performance Between Categoriesmentioning
confidence: 99%
“…Xiao et al referenced 3 studies that they argued were inconsistent with the findings of our study . In the 3 retrospective studies, the study investigators compared treatment outcomes between patients treated with neoadjuvant CRT compared with POC.…”
mentioning
confidence: 52%